Mechanical support of pulmonary blood flow as a strategy to support the Norwood circulation-lumped parameter model study. (2nd May 2022) - Peer, Syed Murfad; Yildirim, Canberk; Desai, Manan; Ramakrishnan, Karthik; Sinha, Pranava; Jonas, Richard; Yerebakan, Can; Pekkan, Kerem
Abstract: OBJECTIVES: We hypothesize that mechanical assistance of the pulmonary blood flow in a Norwood circulation can increase systemic blood flow and oxygen delivery. The aim of the study was to compare haemodynamics of an unassisted Norwood Blalock–Taussig shunt circulation with a mechanically assisted pulmonary flow-based Norwood circulation, using a lumped parameter computational model. METHODS: A neonatal circulatory lumped parameter model was developed to simulate a Norwood circulation with a 3.5-mm Blalock–Taussig shunt in a 3.5-kg neonate. A roller pump circulatory assist device with an inflow bladder was incorporated into the Norwood circulation to mechanically support the pulmonary circulation. Computer simulations were used to compare the haemodynamics of the assisted and unassisted circulations. Assisted and unassisted models with normal (56%) and reduced ejection fraction (30%) were compared. RESULTS: Compared to the unassisted Norwood circulation, the systemic flow in the assisted Norwood increased by 25% (ejection fraction = 56%) and 41% (ejection fraction = 30%). The central venous pressure decreased by up to 3 mmHg (both ejection fraction = 56% and ejection fraction = 30%) at a maximum pulmonary assist flow of 800 ml/min. Initiation of assisted pulmonary flow increased the arterial oxygen saturation by up to 15% and mixed venous saturation by up to 20%. CONCLUSIONS: This study demonstrates that an assisted pulmonary flow-based Norwood circulation has higher systemic flow and oxygen delivery compared to a standard Norwood Blalock–Taussig shunt circulation. Abstract : Norwood operation is the most utilized surgical stage 1 palliation strategy for patients with hypoplastic left heart syndrome (HLHS).